Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Prestasi Kerja Karyawan Balai Latihan Kerja (BLK) Pertanian Klampok di Banjarnegara - FITRIANINGSIH, DIAH; , Dra. Titik Asmawati, SE, M.Si (2015)
ABSTRACT Diah Fitrianingsih / A210110188; INFLUENCE OF LEADERSHIP STYLE AND MOTIVATION ACHIEVEMENT EMPLOYEES WORKING ON WORK TRAINING CENTER (BLK) Klampok IN AGRICULTURAL BANJARNEGARA. Thesis, Faculty of Teacher Training and Education, University of Muhammadiyah Surakarta. October, 2015 The purpose of this study was to determine the effect: 1) leadership style on employee performance, 2) work motivation on employee performance, 3) leadership style and work motivation on employee performance. This research is a descriptive quantitative research. The research population is all employees who totaled 63 with sample of 55 employees was taken with proportionate stratified random sampling technique. Data collected by questionnaire. Questionnaire tested the validity and reliability as well as the test requirements of the data analysis technique used is multiple linear regression analysis, t test, F test, ujiR2 and the relative contribution and effective. The results using regression analysis regression equation Y = 10.888 + 0,692X1 + 0,655X2, which means there are significant variables X1 (leadership style) and X2 (work motivation) to Y (employee performance). The research found that: 1) there is positive and significant influence of leadership style on employee performance is evidenced by the positive regression coefficient 0,692bernilai and obtained t> t table is 5.563> 2.006 and the significance value <0.05 is 0.000; 2) there is a positive and significant effect of work motivation on employee performance is evidenced by 0.655 regression coefficient is positive and obtained t> t table is 3,36> 2.006 and the significance value <0.05 is 0.001; 3) there is a positive and significant effect of leadership style and work motivation on employee performance proven results Fhitung> Ftable is 38.028> 3.15 and a value of 0.05 is 0,000; 4) the coefficient of determination (R2) of 0.594 obtained indicate that employee performance is influenced by a combination of variables of leadership style and work motivation 59.4% consisting of 39.46% from 19.89% and the leadership style of motivation and the remaining 40 , 6% is influenced by other variables not examined. Keywords: performance, leadership style, employee motivation